A Dynamic Replica Creation and Eviction Mechanism based on Files Dependencies in a Federated Grid Environment - Argungu, Musa Sule; Arif, Suki; Omar, Mohd Hasbullah (2018)
For quite a while, data replication has attracted the attention of many researchers in the field of data grid system, with a few researchers focusing on data replication in a federated data grid environment.The central goal of data replication mechanisms is to improve data locality, by creating more copies of the most popular files, and evicting unpopular files. In the conventional data grid systems, a common practice was to evaluate popular files based on economic approach, which evicts unpopular files based on least frequently or least recently used factor, to create space for incoming file replicas. However, this method tends to ignore the possible logical dependencies among st the replica files, which leads to the inappropriate evaluation of popular /unpopular files and consequently may result to the eviction of files with high logical dependencies on other files that may be needed later by other files or applications. As a resolution to this problem, a dynamic replica creation and eviction mechanism (DRCEM) is proposed by this research work, which considers files logical dependencies, while evaluating popular or unpopular files and before evicting files from the system